2009
DOI: 10.1021/am900030u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conversion on the Structure−Property Relationships of Amine-Cured Epoxy Thermosets

Abstract: The effects of conversion beyond the gel point on the structure-property relationships of epoxy thermosets using formulations representative of the most commonly used epoxy resin and amine curing agents at balanced stoichiometry with an emphasis on the thermal, tensile, and fracture properties were studied. The range of T(g) from just beyond the gel point to full conversion typically is >100 degrees C. Fracture toughness (as K(1c)) of the epoxy thermosets cured with relatively flexible amines such as ethylened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 23 publications
6
56
0
Order By: Relevance
“…Materials that contain opposing glassy-state E' and T g values are said to be antiplasticized, where at temperatures below the glass transition additives can restrict short-range molecular motions and thus stiffen the material. Such hindrances may arise from the filling of free volume and/or an increase in secondary molecular interactions and have been extensively reported for epoxy networks [44][45][46]. The E' trend observed herein is attributed to the network-level incorporation of HBE which provides additional functionality to enhance the network's cohesive forces.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 61%
See 1 more Smart Citation
“…Materials that contain opposing glassy-state E' and T g values are said to be antiplasticized, where at temperatures below the glass transition additives can restrict short-range molecular motions and thus stiffen the material. Such hindrances may arise from the filling of free volume and/or an increase in secondary molecular interactions and have been extensively reported for epoxy networks [44][45][46]. The E' trend observed herein is attributed to the network-level incorporation of HBE which provides additional functionality to enhance the network's cohesive forces.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 61%
“…Hydrogen-bonding networks within polyester hyperbranched polymers have been previously found to impact material properties, and it has been shown that the concentration of these secondary interactions is the key to the observed increases [27]. An increase in non-bond interactions is understood to enhance the network's cohesive energy density, which has been previously shown to improve room temperature modulus [46]. FTIR spectra were taken to confirm that the additional hydroxyl-functionality remains after the HBE-modifier is cured into the network ( Figure 6).…”
Section: Network Mechanical Behaviormentioning
confidence: 99%
“…These parameters drive the final bulk properties of the material through a variety of interactions. Marks and Snelgrove measured decreasing mechanical properties of epoxy‐amine thermosets with increasing conversion . Literature reported results have been consistent in that properties, such as modulus and fracture toughness, diminish as conversion increases from 0.8 to 1.0.…”
Section: Introductionmentioning
confidence: 63%
“…Thus diaminodiphenylsulfone [126,127] (DDS, Fig. 23) can present pot-life of several months, while for diethylenetriamine [127] (DETA, Fig. 23), it could hardly be longer than twenty minutes.…”
Section: Page 16 Of 163mentioning
confidence: 99%